2010
DOI: 10.1038/onc.2010.303
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM4B: A novel cancer-associated gene motivates multidrug resistance through efflux and activating PI3K/AKT signaling

Abstract: LAPTM4B (lysosomal protein transmembrane 4 beta) is a newly identified cancer-associated gene. Both of its mRNA and the encoded LAPTM4B-35 protein are significantly upregulated with more than 70% frequency in a wide variety of cancers. The LAPTM4B-35 level in cancer is evidenced to be an independent prognostic factor and its upregulation promotes cell proliferation, migration and invasion, as well as tumorigenesis in nude mice. In contrary, knockdown of LAPTM4B-35 expression by RNA interference (RNAi) reverses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
116
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 29 publications
7
116
1
Order By: Relevance
“…The inhibition of cell migration and invasion induced by AP4 shRNA was markedly rescued by LAPTM4B overexpression in both cell lines (Figure 4A, B). LAPTM4B has been shown to motivate multidrug resistance by activation the PI3K/AKT signaling pathway [30]. In our study, we detected the effects of PI3K specific inhibitor on AP4 and LAPTM4B associated MDR.…”
Section: Ap4 Promotes Breast Cancer Cell Migration and Invasion Throumentioning
confidence: 51%
See 1 more Smart Citation
“…The inhibition of cell migration and invasion induced by AP4 shRNA was markedly rescued by LAPTM4B overexpression in both cell lines (Figure 4A, B). LAPTM4B has been shown to motivate multidrug resistance by activation the PI3K/AKT signaling pathway [30]. In our study, we detected the effects of PI3K specific inhibitor on AP4 and LAPTM4B associated MDR.…”
Section: Ap4 Promotes Breast Cancer Cell Migration and Invasion Throumentioning
confidence: 51%
“…The PPRP motif in the N-terminus of LAPTM4B-35 protein directly binding to PI3K p85 α subunit could strongly phosphorylate AKT and then motivate MDR in Hela cells [30]. In the present study, we showed that silencing AP4 induced apoptosis and and protein levels were examined in MCF7 and MDA-MB-231 cells exposed to AP4 overexpression vector.…”
mentioning
confidence: 66%
“…It has been confirmed that LAPTM4B protein could upregulate some proliferation-promoting transcription factors such as c-Myc, c-Jun and c-Fos, and cell cycle-promoting proteins such as cyclin D1 and E (28). Meanwhile, it could also activate PI3K/AKT signaling pathway to motivate cellular multidrug resistance (31). A recent study clarified that cAMP responsive element binding protein-1 (CREB1) played an important role in LAPTM4B transcriptional regulation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extensive studies have been performed to account for such outcomes. Studies have shown that upregulation of LAPTM4B could promote cell proliferation (28), invasion, migration (29) and may inhibit cell apoptosis (30,31) in vitro, while in nude mice the time of tumorigenesis was markedly shortened (29). It was assumed that various signal molecules were associated with cellular malignant transformation after the alteration of LAPTM4B protein expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated LAPTM4B mRNA and protein levels have been documented in multiple cancers and cell lines, where they correlate with pathological grade and prognosis in vivo and promote proliferation, migration, invasion, and drug resistance in vitro. 35 In this study, LAPTM4B overexpression was identified in LUAD and LUSC tumor samples compared to normal tissues (Fig. 4), as well as in patients with poor OS in KIRC and LAML (Fig.…”
mentioning
confidence: 99%